Effectiveness and safety of meropenem/clavulanate-containing regimens in the treatment of MDR- and XDR-TB. Issue 4 (10th March 2016) - Tiberi, Simon; Payen, Marie-Christine; Sotgiu, Giovanni; D'Ambrosio, Lia; Alarcon Guizado, Valentina; Alffenaar, Jan Willem; Abdo Arbex, Marcos; Caminero, Jose A.; Centis, Rosella; De Lorenzo, Saverio; Gaga, Mina; Gualano, Gina; et al.
No large study has ever evaluated the efficacy, safety and tolerability of meropenem/clavulanate to treat multidrug- and extensively drug-resistant tuberculosis (MDR- and XDR-TB). The aim of this observational study was to evaluate the therapeutic contribution, effectiveness, safety and tolerability profile of meropenem/clavulanate added to a background regimen when treating MDR- and XDR-TB cases. Patients treated with a meropenem/clavulanate-containing regimen (n=96) showed a greater drug resistance profile than those exposed to a meropenem/clavulanate-sparing regimen (n=168): in the former group XDR-TB was more frequent (49% versus 6.0%, p<0.0001) and the median (interquartile range (IQR)) number of antibiotic resistances was higher (8 (6–9) versus 5 (4–6)). Patients were treated with a meropenem/clavulanate-containing regimen for a median (IQR) of 85 (49–156) days. No statistically significant differences were observed in the overall MDR-TB cohort and in the subgroups with and without the XDR-TB patients; in particular, sputum smear and culture conversion rates were similar in XDR-TB patients exposed to meropenem/clavulanate-containing regimens (88.0% versus 100.0%, p=1.00 and 88.0% versus 100.0%, p=1.00, respectively). Only six cases reported adverse events attributable to meropenem/clavulanate (four of them then restarting treatment). The nondifferent outcomes and bacteriological conversion rate observed in cases who were more severe than controls might imply that meropenem/clavulanate could be active in treating MDR- and XDR-TB cases. Meropenem/clavulanate is effective and safe to treat MDR- and XDR-TB in comparison with controls http://ow.ly/XG75j